THE PLACE OF SHEIKH ABBAS VALI IN THE HISTORY OF THE LEFT-BANK KYAT QALA (TAMADDUN NURI JURNALI, 2024)
This article is dedicated to the important role of Sheikh Abbas Wali in the history of the left bank of Kat-Kala. The researches, conducted by G.P.Snesarev with the representatives of the local population near this monument and in Beruni city on the right bank of the Amudarya river, testifies the relation direct of the history of the left-bank Kyat-qala with the the ancient capital Kyat. In particular, the abundance of the myths and legends associated with Sheikh Abbas Vali in studies indicates how important this character was in the history of these monuments.